Basic aspects of professional training of future specialists in physical rehabilitation in Poland - Bielicova N.O (Kharkov National Pedagogical University, 2010)
The basic going is analysed near the system of training of professional personnels on a physical rehabilitation (to physical therapy) in Poland. Legal frameworks of profession of physical internist are exposed. The substantive provisions of the State educational standard are reflected to direction of preparation Physiotherapy. The features of acquisition of specialization for the master's degrees of physical therapy and physical rehabilitation are presented. Basic differences between the systems of preparation of physical internists in Poland and Ukraine represent priorities of social policy and health protection of these countries.